PENINGKATAN KOMPETENSI LITERASI DAN KECAKAPAN DIGITAL HIMPUNAN MAHASISWA ADMINISTRASI PUBLIK (HMAP) UNU PURWOKERTO - Ariesta Amanda; Dian Nastiti (LPPM Universitas Bina Bangsa, 2022)
The digital world is now part of our daily life. Various facilities and We often use the applications available on our devices to search for information solutions to our everyday problems. One that is considered urgent to be pushed the improvement is the ability to think critically about media and data. The development of hoax information makes students a vulnerable group, be it victims or suspects in spreading hoaxes. One of the groups potentially exposed to this issue is the UNU Purwokerto Public Administration Student Association (HMAP). The purpose of carrying out this activity is in response to the increase in hoax issues among students which is troubling, even now students are not only victims but also perpetrators of the spread of hoax issues themselves. The methods used to address partner problems are (1) providing counseling or outreach about the benefits of having literacy competence and digital skills to combat hoax issues, (2) providing training on using information search engines, how to use and select data, (3) providing training how to use chat apps and social media. The results obtained are that there is an increase in literacy competence and digital skills as a digital literacy agent reaching 70% by measuring the pretest questionnaire and post test training activities. The outputs and outcomes of this activity have shaped HMAP as a digital literacy agent capable of breaking the chain of issues spreading hoax news among the public student